PENGARUH MODEL INKUIRI TERBIMBING DENGAN DIAGRAM V (VEE) DALAM PEMBELAJARAN BIOLOGI TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA - Hapsari, Dwi Pertiwi; Sudarisman, Suciati; Marjono, Marjono (Pendidikan Biologi, 2012)
ABSTRACT ? The purpose of this research are: 1) to ascertain the influence of guided inquiry models with diagram V (Vee) on biology learning toward critical thinking skills of 10thgrade students at SMA Negeri Gondangrejo in academic year 2011/2012, 2) to ascertain the influence of guided inquiry models with diagram V (Vee) on biology learning toward learning achievement of 10thgrade students at SMA Negeri Gondangrejo in academic year 2011/2012. The research was quasi experiment research using quantitative approach. The research was designed using posttest only control design. The populations of this research were all of 10thdegree students at SMA Negeri Gondangrejo Karanganyar in academic year 2011/2012. The sample of this research was established by cluster random sampling. The samples of this research were the students of 10th-1 as experiment group and 10th-2 as control group. Experimental group applied guided inquiry models with diagram V (Vee). Control group applied conventional learning models specifically speech varies with experiment accompanied a simple summary. The data was collected by document, test, observation form, and questionnaire. The hypothesis analyzed by t-test with help of SPSS 16. The research concluded that the influence of guided inquiry models with  diagram V (Vee) on biology learning had significant effect toward critical thinking skills of 10thgrade students at SMA Negeri Gondangrejo in academic year 2011/2012 with significant value is 0,041. The influence of guided inquiry models with diagram V (Vee) on biology learning had significant effect toward learning achievement of 10thgrade students at SMA Negeri Gondangrejo in academic year 2011/2012 with significant value cognitive domain is 0,013; psychomotor domain is 0,000 by observation form and 0,001 by questionnaire; affective domain is 0,000 by observation form and 0,005 by questionnaire. Keywords: Guided Inquiry Models, Diagram V (Vee), Critical Thinking Skills, Biology Learning Achievement